Adaptive Programming and going with the grain: IMAGINE's new water gov ernance model in Goma, DRC - Kirk, Tom; Green, Duncan; Stys, Patrycja; Mosquera, Tom (Development Policy Review, 2023)
Motivation This paper explores adaptive approaches to development prog rammes that aim at improving service provision in underperforming sect ors in fragile and conflict affected states (FCAS). It does this throu gh a case study of the Integrated Maji Infrastructure and Governance I nitiative for eastern Democratic Republic of the Congo's (IMAGINE) pub lic-private partnership model for water provision. Purpose The process es and decisions that culminated in IMAGINE's model emphasize the need for programming that is culturally and politically aware, responsive to events, learns in real-time, is entrepreneurial, and works with the grain of local institutions to support change. Detailed case studies of such ways of working are crucial for programmes that seek to challe nge and reform the status quo in FCAS. Methods and approach The paper is based on 42 semi-structured interviews conducted in the summers of 2019 and 2020. They reflect the broad spectrum of actors – individuals , public authorities, and organisations – involved in IMAGINE's evolut ion. Findings The narrative focuses on IMAGINE's attempts to professio nalise and commercialise Goma's water sector. It shows how as IMAGINE repeatedly adapted to ground realities, it took on the characteristics of a public authority, thereby, engendering backlashes that threated its longer-term goals. However, by revisiting its initial values and l ogics it was able to get things done and achieve it aims. Policy impli cations IMAGINE's story suggests that adaptive programmes should put p olitically savvy local development professionals in key positions and enable them to carefully construct coalitions of allies across the sys tems they aim to disrupt. This may also require them to revisit and ad apt their initial ideas, guiding principles and values as greater unde rstandings of development problems are gained. A pubic authorities len s, attuned to the logics programmes seek to address and introduce to F CAS, may help analysts to foreground the implications of such adaptati ons.